Salumpuwit, bangko, silya, atbp. chairs in Filipino life - Lico, Gerard Rey A. (The National Commission for Culture and the Arts, 2012)
Where do we sit? How do we sit? Why do we sit? The book counts the ways. And this is just but the first sitting in the exploration of the many context within which the Philippine chair finds its place in the furniture of history.